SYNTHESIS OF Fe2O3-MONTMORILLONITE AND ITS APPLICATION AS A PHOTOCATALYST FOR DEGRADATION OF CONGO RED DYE - Karna Wijaya; Iqmal Tahir; Nanik Haryanti (Indonesian Journal of Chemistry, 2005)
The preparation of Fe2O3-montmorillonite and it's application as a catalyst for congo red dye photodegradation has been carried out. Fe2O3-montmorillonite was prepared by mixing the iron complexes pillaring agent and montmorillonite. The product was calcined at 250 oC for 5 hours. Montmorillonite and calcined product was analyzed by X-ray diffractometry (X-RD), infrared spectrophotometry (FTIR), gas  sorption analyser, X-ray fluorescense (X-RF) and UV/Vis diffuse reflectance spektrophotometry (UV-DRS). Fe2O3-montmorilonite then was used as a catalyst on congo red dye photodegrdation by UV-illuminating a mixture of 50 mg Fe2O3-montmorillonite and 25 mL congo red 10-4M at 365 nm at various illuminating times. Adsorption of congo red on Fe2O3-montmorillonite and montmorillonite was also performed as a comparison.Result of X-RD analysis showed that the 001 reflection of  Fe2O3-montmorillonite was not  detected that probably indicating the formation of house of card stucture and this result was supported also by the analysis result of distribution of pores and SEM photography result. Results of the XRF analysis showed that iron content increased  from 5.21 % (w/w) in montmorillonite to 25.12 % (w/w) in Fe2O3-montmorillonite. UV- DRS analysis showed the increament of band gap energy from 3.69 eV in the iron oxide bulk to 3.8 eV in Fe2O3-montmorillonite. Specific surface area of the montmorillonite also increased significantly from 69,71 m2/g to 126,49 m2/g and total pores volume increased from 50.70x10-3 mL/Å/g  to 107.89x10-3 mL/Å/g, respectively. Photodegradation of congo red using Fe2O3-montmorillonite caused the decreament of congo red concentration up to 90.22 %  on UV illumination for 60 minutes. Adsorption of congo red on Fe2O3-montmorillonite reached 84.4% and on  montmorillonite was 75.15 %.